Novel mouse model for primary uveal melanoma: a pilot study. (7th September 2016) - Süsskind, Daniela; Hurst, José; Rohrbach, Jens Martin; Schnichels, Sven
Abstract: Background: To establish a mouse model with the aim of studying the tumour biology and metastasis formation of uveal melanoma. Methods: Two human primary uveal melanoma cell lines (UMT2 and UMT42) were injected into the choroid of BALB/c nude mouse eyes. Intraocular tumour growth and metastasis formation in the liver and lungs were assessed after 13 to 22 weeks. Formalin‐fixed, paraffin‐embedded material was processed via haematoxylin and eosin staining for histological examination and periodic acid Schiff staining to search for extravascular matrix patterns. Immunohistochemistry for Melan A, CD34 and Ki67 was performed to assess the expression of a melanocytic lineage marker, angiogenesis and proliferative activity. Results: All eyes injected with UMT2 cells, but only 25% of eyes treated with UMT42, developed intraocular tumour growth. The morphology of intraocular melanomas resembled that of primary tumours and showed signs of malignancy, including retinal invasion, optic nerve invasion and scleral penetration with extraocular tumour growth. UMT2 tumours formed extravascular matrix patterns exclusively. Most of the tumour cells expressed Melan A. Intratumoural angiogenesis was detected in both tumour entities. Proliferative activity was verified in all but one tumour. However, no metastases appeared in the liver or lungs. Conclusions: The mouse model presented with the UMT2 cell line allows for investigations of tumour biology of the primary UM because of the high degree of similarity between the tumours generated in the mouse eyes and the corresponding primary human UM. Unfortunately, the model is not suitable for investigations of metastasis formation.